Study of Ichthyofaunal Diversity with Reference to Water Quality in Lower Lake of Bhopal, India - Somashree Bhakta; Shriparna Saxena (Archives of Current Research International, 2025)
Background: Biodiversity is the concept of variety and variability of living organisms. Biodiversity includes not only the variety of species but also include genetic diversity, habitats, and ecological communities. Preserving biodiversity is crucial for protecting nature and ensuring a future for generations. Advancements in technologies as like remote sensing; robotic equipment improved our understanding of biodiversity on levels from genes to ecosystems. Aim: The present study examined the ichthyofaunal diversity and several ecological influencers of the diversity in the Lower Lake, Bhopal, during 2023-2024. Materials and Method: A total of 19 species of fish were recorded across 6 orders, and 9 families, all indication a taxonomically diverse assemblage. For water quality parameters, water was collected from the sampling station in the mornings between 7 am and 11 am of each month. Air temperature, water temperature, pH, DO, CO2, total alkalinity, and total hardness were recorded. The Shannon–Wiener Diversity Index, Margalef’s Richness Index and Simpson’s Diversity Index was measured for estimation of biodiversity of fish species in various habitats of the lake. Results and Discussion: The fish community is primarily dominated by Cypriniformes (65%) and followed by Ophiocephaliformes (15%) and Perciformes (10%), with the others being negligible. The prominent species were Labeo rohita, Labeo catla, and Cyprinus carpio, all which have economic significance. Most of the species present in the study area were Least Concern (LC) by IUCN, except for Cyprinus carpio (VU) and Mystus vittatus (NT). Diversity analysis indicated that the fish diversity was strongest in the winter due to substantial species richness and evenness, as observed with higher Shannon (H = 2.835) and Simpson (1-D = 0.9357) diversity indices and less dominance in the fish communities. Correlation analysis of the data found that physicochemical variables like temperature and pH, and dissolved oxygen are closely co-distributed with key species distribution. Generalist trophic levels, such as the Siluriformes and Cypriniformes eating and feeding simplicity likely increased their presence due to high ecological flexibility than the other orders of fish which likely occupied similar space but had less representation due to habitat selection, or low tolerance to fluctuations in environmental conditions. Conclusion: The research emphasizes the effects of seasonal variation and human-induced management, and stresses fish community composition in urban wetlands, thus accenting the need for habitat preservation and water quality management to support aquatics biodiversity. The study will help to understand the present status of fish diversity in Lower Lake (Ramsar Site), one of the twine lake of Bhoj Wetland.